Community health worker intervention to reduce worker exposure to volatile organic compounds in small business auto and beauty shops in a marginalized community: A cluster randomized controlled trial - Shannon L. Gutenkunst; Nathan Lothrop; Carolina Quijada; Marvin Chaires; Imelda Cortez; Flor Sandoval; Jella Balgos; Emma V. Gallardo; Pedro Flores Gallardo; Sam Sneed; Jenna K. Honan; Karla Bayless; et al. (PLoS ONE, 2026)
Background Occupational diseases affect many workers in the United States, with Latinos disproportionately affected. Small businesses face barriers to implementing workplace health protections that community health workers (CHWs) may help overcome. The objective of this study was to determine whether a CHW-led industrial hygiene intervention could reduce volatile organic compound (VOC) exposure in small auto repair and beauty shops that primarily employ marginalized workers. Methods In this two-arm, parallel, cluster randomized trial, small business (≤25 employees) auto repair and beauty shops in Tucson, AZ were randomized to immediate or delayed intervention, stratified by sector. CHWs assessed shops and provided knowledge of controls and $300 for new ones. Total VOCs (TVOCs) were measured using photoionization detectors placed on or near participants. The primary outcome was the change in TVOCs at the shop level after the intervention, assessed across three timepoints with four workshift measurements per assessment. Mixed-effects models accounted for clustering by shop. Results We enrolled 38 auto repair shops and 46 beauty shops (73% Latino workers) and analyzed 846 workshift measurements at 236 shop assessments. Adjusted models showed a non-statistically significant intervention effect: auto shops experienced on average an estimated 28% TVOC increase (95% CI: −46% to 203%); beauty shops experienced on average an estimated 27% reduction (95% CI: −55% to 19%). Beauty shops had TVOC concentrations about 10 times higher than auto shops, and 87% of their assessments had ventilation rates below the recommended minimum. Conclusions Although not statistically significant, the CHW-led intervention may meaningfully reduce VOC exposure in beauty shops. High TVOC concentrations and inadequate ventilation in beauty shops highlight the need for targeted interventions and policy changes to improve the air quality in these underserved small businesses. Trial registration This trial was registered with clinicaltrials.gov ( NCT03455530 ) on March 6, 2018.